Variation in stem bark conductance to water vapor in Neotropical plant species - Ávila-Lovera, Eleinis; Winter, Klaus (Frontiers in Forests and Global Change, 2024)
Bark conductance to water vapor (gbark) is an important determinant of drought tolerance in tropical plants. Examining species differences in bark conductance can provide useful information about the resilience of tropical trees to ongoing climate change. Values of gbark are positively related to stem photosynthetic rate in desert species, showing that increased stem photosynthesis capacity is associated with increased bark conductance to water vapor. We determined whether stem morphometric traits, bioclimatic variables (e.g., temperature and precipitation), and shared evolutionary history help explain variation in gbark among tropical plant species. We surveyed 94 species (90 tree and 4 liana species) from lowland and mid-elevation forests in Panama and estimated gbark, stem diameter, specific stem area, bark thickness, sapwood area, and bark and wood density. Climate data was extracted from CHELSA 2.1 and Instituto de Meteorología e Hidrología de Panamá. Phylogenetic signal was estimated using Blomberg’s K statistic and Pagel’s λ. Bark conductance decreased with increases in bark thickness and was positively related to mean annual precipitation and mean annual temperature. We also determined the temperature response of gbark of six plant species (five trees and one liana) from a lowland forest. In all six species, gbark decreased as air temperature increased from 20 to 50°C. There was a significant phylogenetic signal in gbark, with closely related species resembling each other more than distantly related species. We conclude that interspecific differences in gbark of Neotropical tree species depend on all three factors studied: stem morphometry, climate, and evolutionary history.